KEPEMIMPINAN, MOTIVASI KERJA PEGAWAI DAN KUALITAS PELAYANAN - ', Kamaluddin (Jurnal Ilmu Administrasi Negara, 2016)
Leadership, Motivation Work On Service Quality. The purpose of this study was to identify and analyze the extent of the leadership and motivation of employees affects the quality of health services provided at the health center Kundur West. The sampling technique used in this study is a census because of all the population sampled, the entire Civil Servants (PNS) amounted to 35 and people who are getting health care as a sample. Methods of data collection through interviews, questionnaires and documentation study. Methods of data analysis using multiple linear regression using SPSS. The results showed that simultaneous and partial leadership and employee motivation positive and significant impact on the quality of services provided by employees. Besides, the respondents (public) state is good about the quality of service. The value of coefficient of determination (R2) was obtained from this study at 89.3% of people, which means the leadership and motivation of employees to explain the effect on the variable quality of health services, while the remaining 10.7% is influenced by other variables not examined. The results of research known leadership variable is the dominant variable affecting the quality of service in this study.